The Influence Of Individual And Occupational Characteristics On Employee Commitment With Job Satisfaction As A Mediation At Pt. State Electricity Company (Persero) PLN UP3 Medan - Reza, Reza Ikhsandy (Amkop Management Accounting Review (AMAR), 2025)
This study aims to examine the influence of individual characteristics and job characteristics on employee work commitment with job satisfaction as a mediating variable at PT PLN (Persero) UP3 Medan. The research uses an associative quantitative method with a Structural Equation Modeling (SEM) approach using SmartPLS software. The results show that both individual characteristics and job characteristics have a positive and significant influence on job satisfaction. Job satisfaction also significantly influences employee commitment. Furthermore, there is a significant indirect effect of individual and job characteristics on employee commitment through job satisfaction as a mediating variable. These findings highlight the importance of understanding and managing individual and job characteristics to improve employee satisfaction and commitment within the organization.